The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.neuropsychologia.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Sleep spindles provide indirect support to the consolidation of emotional encoding contexts

Abstract: Emotional memories tend to be strengthened ahead of neutral memories during sleep-dependent consolidation. In recent work, however, we found that this is not the case when emotion pertains to the contextual features of a memory instead of its central constructs, suggesting that emotional contexts are influenced by distinct properties of sleep. We therefore examined the sleep-specific mechanisms supporting representations of emotional context and asked whether these differ to those already implicated in central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 64 publications
(86 reference statements)
1
17
0
Order By: Relevance
“…As summarized by Cellini and Parma (2015), re-exposing participants during SWS to a cue previously matched with a threatening stimulus, successfully enhances fear extinction in humans. Other studies showed direct (Kaestner, et al, 2013) or indirect evidence (Cairney, Durrant, Hulleman, & Lewis, 2014a;Cairney, et al, 2014b) of a relationship between sleep spindles and emotional memory. Notably, Cairney and colleagues (2015) reported a positive association between the proportion of SWS and the consolidation of unpleasant pictures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized by Cellini and Parma (2015), re-exposing participants during SWS to a cue previously matched with a threatening stimulus, successfully enhances fear extinction in humans. Other studies showed direct (Kaestner, et al, 2013) or indirect evidence (Cairney, Durrant, Hulleman, & Lewis, 2014a;Cairney, et al, 2014b) of a relationship between sleep spindles and emotional memory. Notably, Cairney and colleagues (2015) reported a positive association between the proportion of SWS and the consolidation of unpleasant pictures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in two recent studies, human participants were selectively re-exposed during NREM to sounds or odors previously matched with a threatening stimulus and, as a result, fear extinction was successfully enhanced (Ai, Chen, Liu, He, Xue, Bao et al, 2015;Hauner, Howard, Zelano, & Gottfried, 2013;He, Sun, Li, Zhang, Shi, Ai et al, 2015). Furthermore, studies found associations between sleep spindles and the consolidation of emotional information (Cairney, Durrant, Jackson, & Lewis, 2014b;Kaestner, Wixted, & Mednick, 2013). Moreover, in another study, Cairney and colleagues (2015) showed a positive relationship between the proportion of SWS and memory consolidation of unpleasant pictures.…”
Section: Introductionmentioning
confidence: 99%
“…Although originally implicated in procedural learning, sleep spindles have been linked with the consolidation of a host of memory types, including emotional and declarative memory. For example, higher spindle activity in a mid-day nap was linked to enhanced consolidation of an associative task [17] and was also shown to moderate emotional memory consolidation [73]. In preschool-aged children, we demonstrated that higher spindle density in habitual nappers was correlated with enhanced consolidation of a visuo-spatial task [31].…”
Section: Naps Benefit Cognitive Functionsmentioning
confidence: 99%
“…Despite these converging findings, several studies failed to establish associations between REMS physiology and emotional memory performance [33][34][35][36], leaving ambiguities regarding the role of REMS in emotional memory consolidation. Critically, a considerable number of studies did not even replicate selective retention benefits of emotional memories across sleep [37][38][39].…”
Section: Sleep and Emotional Memorymentioning
confidence: 99%